The Real-Life Effectiveness and Safety of Omalizumab Updosing in Patients With Chronic Spontaneous Urticaria - SALMAN, ANDAÇ; CÖMERT ÖZER, ELİF (SAGE PUBLICATIONS INC, 2019)
Background: Omalizumab is a third-line treatment for chronic spontaneous urticaria (CSU). Studies investigating the use of higher doses of omalizumab in patients unresponsive to regular doses are limited. Objectives: This study aims to investigate the effectiveness and safety of omalizumab 450 mg in CSU. Methods: A retrospective cohort study was conducted. The response to therapy was evaluated using the Urticaria Activity Score over 7 days (UAS7) and the Urticaria Control Test (UCT). Patients showing complete response (CR) (UAS7: 0-1) to omalizumab 300 mg (Group 1) and patients receiving at least 3 doses of omalizumab 450 mg (Group 2) between 2016 and 2018 were included. Results: A total of 72 patients (Group 1: 59; Group 2: 13) were included. In Group 2, the mean UAS7 score decreased from 18.6 to 5.1 and the mean UCT score increased from 8.6 to 12 after a mean 4.3 courses of 450 mg omalizumab treatment. Of the 13 patients in Group 2, 6 had CR and 3 had good disease control (UAS7: 2-6). The rate of patients with low baseline IgE levels (< 43 IU/mL) was significantly higher in Group 2. Conclusions: Higher doses of omalizumab are effective and safe in patients with CSU that is unresponsive to omalizumab 300 mg. Lower baseline total IgE levels might be used as a predictor of nonresponse to omalizumab and the need for higher doses.
Keywords: chronic spontaneous urticaria; omalizumab; updosing; MINIMAL IMPORTANT DIFFERENCE; DISEASE-ACTIVITY; IGE LEVELS; MANAGEMENT; DIAGNOSIS; GUIDELINE